Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Sure, let's find each of the compositions step-by-step:
(a) [tex]\( f \circ g \)[/tex]:
[tex]\( f \circ g(x) \)[/tex] means we apply [tex]\( g \)[/tex] first and then apply [tex]\( f \)[/tex] to the result.
Given [tex]\( g(x) = x - 6 \)[/tex]:
1. First apply [tex]\( g \)[/tex]:
[tex]\[ g(x) = x - 6 \][/tex]
2. Now substitute [tex]\( g(x) \)[/tex] into [tex]\( f \)[/tex]:
[tex]\[ f(g(x)) = f(x - 6) \][/tex]
3. Since [tex]\( f(x) = x^2 \)[/tex], replace [tex]\( x \)[/tex] with [tex]\( x - 6 \)[/tex]:
[tex]\[ f(x - 6) = (x - 6)^2 \][/tex]
So,
[tex]\[ f \circ g(x) = (x - 6)^2 \][/tex]
(b) [tex]\( g \circ f \)[/tex]:
[tex]\( g \circ f(x) \)[/tex] means we apply [tex]\( f \)[/tex] first and then apply [tex]\( g \)[/tex] to the result.
Given [tex]\( f(x) = x^2 \)[/tex]:
1. First apply [tex]\( f \)[/tex]:
[tex]\[ f(x) = x^2 \][/tex]
2. Now substitute [tex]\( f(x) \)[/tex] into [tex]\( g \)[/tex]:
[tex]\[ g(f(x)) = g(x^2) \][/tex]
3. Since [tex]\( g(x) = x - 6 \)[/tex], replace [tex]\( x \)[/tex] with [tex]\( x^2 \)[/tex]:
[tex]\[ g(x^2) = x^2 - 6 \][/tex]
So,
[tex]\[ g \circ f(x) = x^2 - 6 \][/tex]
(c) [tex]\( g \circ g \)[/tex]:
[tex]\( g \circ g(x) \)[/tex] means we apply [tex]\( g \)[/tex] first and then apply [tex]\( g \)[/tex] again to the result.
Given [tex]\( g(x) = x - 6 \)[/tex]:
1. First apply [tex]\( g \)[/tex]:
[tex]\[ g(x) = x - 6 \][/tex]
2. Now substitute [tex]\( g(x) \)[/tex] into [tex]\( g \)[/tex]:
[tex]\[ g(g(x)) = g(x - 6) \][/tex]
3. Since [tex]\( g(x) = x - 6 \)[/tex], replace [tex]\( x \)[/tex] with [tex]\( x - 6 \)[/tex]:
[tex]\[ g(x - 6) = (x - 6) - 6 = x - 12 \][/tex]
So,
[tex]\[ g \circ g(x) = x - 12 \][/tex]
Therefore, the detailed solutions are:
(a) [tex]\( f \circ g(x) = (x - 6)^2 \)[/tex]
(b) [tex]\( g \circ f(x) = x^2 - 6 \)[/tex]
(c) [tex]\( g \circ g(x) = x - 12 \)[/tex]
(a) [tex]\( f \circ g \)[/tex]:
[tex]\( f \circ g(x) \)[/tex] means we apply [tex]\( g \)[/tex] first and then apply [tex]\( f \)[/tex] to the result.
Given [tex]\( g(x) = x - 6 \)[/tex]:
1. First apply [tex]\( g \)[/tex]:
[tex]\[ g(x) = x - 6 \][/tex]
2. Now substitute [tex]\( g(x) \)[/tex] into [tex]\( f \)[/tex]:
[tex]\[ f(g(x)) = f(x - 6) \][/tex]
3. Since [tex]\( f(x) = x^2 \)[/tex], replace [tex]\( x \)[/tex] with [tex]\( x - 6 \)[/tex]:
[tex]\[ f(x - 6) = (x - 6)^2 \][/tex]
So,
[tex]\[ f \circ g(x) = (x - 6)^2 \][/tex]
(b) [tex]\( g \circ f \)[/tex]:
[tex]\( g \circ f(x) \)[/tex] means we apply [tex]\( f \)[/tex] first and then apply [tex]\( g \)[/tex] to the result.
Given [tex]\( f(x) = x^2 \)[/tex]:
1. First apply [tex]\( f \)[/tex]:
[tex]\[ f(x) = x^2 \][/tex]
2. Now substitute [tex]\( f(x) \)[/tex] into [tex]\( g \)[/tex]:
[tex]\[ g(f(x)) = g(x^2) \][/tex]
3. Since [tex]\( g(x) = x - 6 \)[/tex], replace [tex]\( x \)[/tex] with [tex]\( x^2 \)[/tex]:
[tex]\[ g(x^2) = x^2 - 6 \][/tex]
So,
[tex]\[ g \circ f(x) = x^2 - 6 \][/tex]
(c) [tex]\( g \circ g \)[/tex]:
[tex]\( g \circ g(x) \)[/tex] means we apply [tex]\( g \)[/tex] first and then apply [tex]\( g \)[/tex] again to the result.
Given [tex]\( g(x) = x - 6 \)[/tex]:
1. First apply [tex]\( g \)[/tex]:
[tex]\[ g(x) = x - 6 \][/tex]
2. Now substitute [tex]\( g(x) \)[/tex] into [tex]\( g \)[/tex]:
[tex]\[ g(g(x)) = g(x - 6) \][/tex]
3. Since [tex]\( g(x) = x - 6 \)[/tex], replace [tex]\( x \)[/tex] with [tex]\( x - 6 \)[/tex]:
[tex]\[ g(x - 6) = (x - 6) - 6 = x - 12 \][/tex]
So,
[tex]\[ g \circ g(x) = x - 12 \][/tex]
Therefore, the detailed solutions are:
(a) [tex]\( f \circ g(x) = (x - 6)^2 \)[/tex]
(b) [tex]\( g \circ f(x) = x^2 - 6 \)[/tex]
(c) [tex]\( g \circ g(x) = x - 12 \)[/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.
What steps did US President Bill Clinton take to attempt to secure Bosnia and keep the peace there?.